Drug Addiction, De-Addiction & Crime (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
Drug addiction has become a major social problem in almost all countries. It is spread over all the age groups irrespective of financial background and gender. Most crimes result from a variety of factors (personal, situational, cultural, economic); even when drugs are a cause, they are likely to be only one factor among many. While drug trafficking is severely punishable with a minimum of ten years of imprisonment (Section 21 of Narcotic Drugs and Psychtropic Substances Act 1985), drug consumption also is punishable with six months of imprisonment (Section 27 of the NDPS Act 1985).
Keywords: Alcohol; Criminal Homicide